Female Sexual Dysfunction and the Placebo Effect: A Meta-analysis. Issue 2 (August 2018) - Weinberger, James M.; Houman, Justin; Caron, Ashley T.; Patel, Devin N.; Baskin, Avi S.; Ackerman, A. Lenore; Eilber, Karyn S.; Anger, Jennifer T.
Abstract : OBJECTIVE: To quantify the placebo effect of various pharmacologic modalities including neuromodulators, hormonal agents, and onabotulinum toxin A for female sexual dysfunction. DATA SOURCES: Using Meta-analyses Of Observational Studies in Epidemiology guidelines, we conducted a systematic review of PubMed, EMBASE, ClinicalTrials.gov, and the Cochrane Review databases. METHODS OF STUDY SELECTION: Eleven search terms, "female sexual dysfunction" "treatment" in combination with "hypoactive sexual desire, " "arousal disorder, " "sexual pain disorder, " "genitourinary syndrome of menopause, " "orgasmic disorder, " "vulvovaginal atrophy, " "vaginismus, " "vaginal atrophy, " "vulvodynia, " and "vestibulitis, " were used. Studies were included if their design was randomized, included a placebo arm, and used the Female Sexual Function Index as an outcome measure. TABULATION, INTEGRATION, AND RESULTS: The placebo effect on the Female Sexual Function Index was compared with each respective study's treatment effect using inverse-variance weighting in a random-effects analysis model. Six hundred five relevant articles were retrieved. Twenty-four randomized controlled trials included a placebo arm. Of these, eight studies used the Female Sexual Function Index. Across these studies, 1, 723 women with clinical pretreatment female sexual dysfunction received placebo. Two thousand two hundred thirty-six women were in the treatment arm of the respective studies and received various pharmacologic interventions including flibanserin, bupropion, onabotulinum toxin A, intravaginal prasterone, intranasal oxytocin, ospemifene, and bremelanotide. Women receiving placebo improved 3.62 (95% CI 3.29–3.94) on the Female Sexual Function Index. The treatment arm had a corresponding increase of 5.35 (95% CI 4.13–6.57). CONCLUSION: This meta-analysis of Level I evidence demonstrates that 67.7% of the treatment effect for female sexual dysfunction is accounted for by placebo. Our findings suggest that the current treatments for female sexual dysfunction are, overall, minimally superior to placebo, which emphasizes the ongoing need for more efficacious treatment for female sexual dysfunction. Abstract : Evidence indicates that 67.7% of the treatment effect for female sexual dysfunction can be accounted for by placebo.